2015
DOI: 10.1177/1535370215597194
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition: An emerging target in tissue fibrosis

Abstract: Epithelial-mesenchymal transition (EMT) is involved in a variety of tissue fibroses. Fibroblasts/myofibroblasts derived from epithelial cells contribute to the excessive accumulation of fibrous connective tissue in damaged tissue, which can lead to permanent scarring or organ malfunction. Therefore, EMT-related fibrosis cannot be neglected. This review highlights the findings that demonstrate the EMT to be a direct contributor to the fibroblast/myofibroblast population in the development of tissue fibrosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 164 publications
(216 reference statements)
2
90
0
1
Order By: Relevance
“…Fibrosis is usually the final pathological state of many chronic inflammatory diseases and may lead to organ dysfunction . Recently, growing evidence suggests that EMT is a direct contributor to the fibroblast/myofibroblast pool during fibrogenesis . EMT can be induced by the joint action of cytokines, inflammation, reactive oxygen species, and many other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is usually the final pathological state of many chronic inflammatory diseases and may lead to organ dysfunction . Recently, growing evidence suggests that EMT is a direct contributor to the fibroblast/myofibroblast pool during fibrogenesis . EMT can be induced by the joint action of cytokines, inflammation, reactive oxygen species, and many other factors.…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level it has been shown that Nrf2 can form a nuclear complex with nuclear pSmad3 at CAGA sites located in the proximal promoters of TGF-β target genes (79), suppressing gene expression (79, 83). Thus, loss of Nrf2 promotes TGF-β/RSmad signaling, a key factor for promoting epithelial-mesenchymal transitions (84). Conversely, TGF-β/RSmad signaling has been shown to suppress Nrf2-dependent gene expression.…”
Section: Nrf2 and Radiation-associated Pulmonary Injurymentioning
confidence: 99%
“…This study found that the ability of cell migration was increased within a short time (≤ 24 h) after c-Ski knockdown, suggesting that H9C2 cells may express some skeletal proteins or turn to fibroblasts after c-Ski silencing. Previous studies have demonstrated that TGF-b, as the best characterized fibrogenic growth factor [21], is markedly and consistently activated in experimental models of cardiac fibrosis [22] and in fibrotic human hearts [23] For nearly a decade, much research showed that EMT is involved in a variety of tissue fibrosis and is a direct contributor to the fibroblast/ /myofibroblast population in the development of tissue fibrosis, such as myocardial, renal and liver fibrosis [24]. TGF-b1-induced EMT can promote myofibroblast transformation, which is prominently involved in the fibrotic processes [9].…”
Section: Discussionmentioning
confidence: 99%